The UK language learning crisis in the public media: a critical analysis. Issue 1 (2nd January 2017) - Lanvers, Ursula; Coleman, James A.
Abstract : Low levels of foreign language learning in the United Kingdom have been attributed to a lack of interest and motivation which, it is claimed, is partly fostered by the media. The present study examines 90 UK newspaper articles that contributed to the public debate on the language learning crisis in the UK between February 2010 and February 2012. Articles were drawn from both national (England, Scotland, Wales, Northern Ireland) and regional newspapers via Nexis UK. Adopting a Critical Discourse Analysis (CDA) theoretical perspective, the authors analyse the themes mentioned in different newspapers, before relating the findings to the target readership demographics of individual newspapers, in order to show how themes identified in particular publications, as well as in the press of the four UK nations, relate to the target readerships and the political context of language policies within England, Scotland, Wales and Northern Ireland.